It's not all about parents' education, it also matters what they do: Parents' employment and children's school success in Germany - Christina Boll; Malte Hoffmann (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
In this paper, we use SOEP data to explore whether parents' employment has an extra effect on the school achievement of their children, beyond the well-established effects of education, income and demography. First, we test whether the source of income or parents' unemployment determine children's school achievements. Second, we analyze the effect of job prestige and factors of societal engagement on children's performance. Our results indicate no clear income associations but the existence of an employment channel as well as a social channel from mothers to their kids. A negative role model for girls is found for maternal housework. Moreover, the fathers' job prestige is substantial.
Keywords: 330